Effect of Kinetin and Budding Date on Top Working for Black Mulberry (Morus nigra L.) - Aziz, Rasul Rafiq; Saleh, Fakhraddin Mustafa Hama; Ahmad, Faraydwn Karim (Sulaimani Journal for Pure and Applied Sciences, 2018)
This study was carried out at Tawella, Located north east of Sulaimani, Iraqi Kurdistan Region in order to determine the effect of two budding date (June 5 and June 20) and three concentrations (0, 5 and 10) mg/l-1 of Kinetin on budding success and growth scion of black mulberry .Results showed that the highest bud success (60%) was obtained on June 20 compared to 50% for June 5 while 5 mg/l-1 Kinetin gave the highest budding success. Interaction of June 5 and 5 mg/l-1 Kinetin resulted in highest budding success (80%). Budding on June 5 gave the highest averages of budshoot length and Number of leaves per budshoot. Kinetin at 5mg/l-1 gave highest budshoot length. Interaction June5 and 5mg/l-1 Kinetin gave the highest budshoot length.
Keywords: Mulberry; Budding dates; Kinetin; budding success